Climate Change and Its Economic Consequences - Veloudos, Giannis (Open Schools Journal for Open Science, 2025)
Imagine you’re walking on a beach that you’ve visited every summer since you were a child. The shoreline is exactly how you remember it—warm sand beneath your feet, seagulls circling overhead, the scent of salt in the air. But after a few years away, you return and something is different: the waves now reach much farther up the beach, the sand looks thinner, and the seawall that once felt safely distant is now dangerously close to the rising tide. That beach, a place of fond memories, has changed—quietly, but unmistakably. This story mirrors what is happening around our planet: subtle but significant changes that accumulate over time. We call this phenomenon climate change—an ongoing alteration of earth’s weather patterns and temperatures, largely influenced by human activities. Today, I want to talk about what climate change is, why it matters to each of us, and how it impacts our communities, our nations, and our future—from both an environmental and an economic standpoint.